Why wastewater treatment fails to protect stream ecosystems in Europe. (15th June 2022) - Büttner, Olaf; Jawitz, James W.; Birk, Sebastian; Borchardt, Dietrich
Highlights: River network positioning of wastewater discharges threatens stream ecosystems. Ecological status in streams declined with higher urban wastewater discharge fraction. Critical threshold of wastewater discharge fraction for stream flow is 6.5% ± 0.5. One third of WWTPs in Europe exceeds the critical threshold. New receiving water-specific strategies for wastewater management are needed. Abstract: There is significant debate about why less than half of European rivers and streams are in good ecological status, despite decades of intense regulatory efforts. Of the multiple stressors that are recognized as potential contributors to stream degradation, we focus on discharge from 26, 500 European wastewater treatment plants (WWTPs). We tested the hypothesis that stream ecological status degradation across Europe is related to the local intensity of wastewater discharge, with an expected stream-order (ω) dependence based on the scaling laws that govern receiving stream networks. We found that ecological status in streams (ω≤3) declined consistently with increasing urban wastewater discharge fraction of stream flow (UDF) across river types and basins. In contrast, ecological status in larger rivers (ω≥4) was not related to UDF. From a continental-scale logistic regression model (accuracy 86%) we identified an ecologically critical threshold UDF = 6.5% ± 0.5. This is exceeded by more than one third of WWTPs in Europe, mostly discharging into smaller streams. Our results suggest that new receiving water-specific strategies for wastewater management are needed to achieve good ecological status in smaller streams.